A BSF Larvae-Based Food Waste Management: A Student-Led Innovation for Wonorejo Village in East Java - Salis Ati Diana; Inaya Sari Melati; Mirza Musyaffa; Atika Fitri; Salsabila Putri Andani (CV. TOTUS TUUS, 2025)
This community service activity was carried out to address the issue of household organic waste accumulation in Wonorejo Village by introducing a sustainable and environmentally friendly solution: the cultivation of Black Soldier Fly (BSF) larvae, commonly known as maggots. The main objective was to educate and empower local residents, particularly women involved in kitchen waste management, through a socialization and training program that promotes maggot-based waste processing. The method of implementation involved direct presentations using PowerPoint slides, followed by discussions, a question-and-answer session, and the distribution of a structured questionnaire to evaluate participants' understanding and motivation. The results indicated a high level of cognitive comprehension among participants regarding the role of maggots in decomposing organic waste and mitigating its environmental impact. Participants also showed a strong sense of responsibility toward environmental protection and a willingness to share their new knowledge. However, motivation to begin maggot cultivation was only moderate, highlighting the need for further technical training and support. The activity demonstrated the potential for maggot farming to reduce food waste by up to 60%, lower methane emissions, and offer additional income opportunities. Nevertheless, cultural stigma and inconsistent waste segregation remain challenges. This initiative revealed that, with proper education and local engagement, sustainable waste management practices can be effectively introduced in rural communities